Voltammetric Determination of Diethylstilbestrol in Pharmaceutical Formulation - Pâmela Caires de Oliveira; Gilberto José Arruda (Orbital: The Electronic Journal of Chemistry, 2019)
A simple, inexpensive and highly sensitive new electrochemical method was developed to quantify Diethylstilbestrol (DES) in medication samples using carbon paste electrode (CPE). The electrode was electrochemically characterized using cyclic voltammetry (CV) and square wave voltammetry (SWV). From the cyclic voltammograms obtained in the presence of diethylstilbestrol could be observed two peaks, one of oxidation at ≈ 590 mV and other of reduction at 200 mV. The development of method for estrogen quantification under study involved optimization of instrumental parameters (frequency, amplitude and potential step) and the experimental parameter pH. The electrochemical procedure applied to diethylstilbestrol was developed using CPE under optimal conditions. Diethylstilbestrol oxidation currents exhibited linear concentration in the 0.017 - 2.08 mmol L-1 range, with a limit of detection of 14.15 nmol L-1. The amount of DES found in the analyzed samples was 0.98 mg, with a relative standard deviation of less than 2%, indicating high agreement with the amount described in the label of the drug (1 mg). The results indicate that the method is applicable for quantifying diethylstilbestrol in pharmaceutical formulation.DOI: http://dx.doi.org/10.17807/orbital.v11i4.1326